QUALITY AND MICROBE PROFILE OF LOCAL AND IMPORT BEEF AT DILI-TIMOR LESTE - V., OLIVEIRA,; KRISTINA DEWI, G.A.M.; SURIASIH, K. (Fakultas Peternakan Universitas Udayana, 2017)
ABSTRACTThis study aims at determining the beef quality and microbes profile of local and import beef marketed at TimorLeste. It is conducted using a completely randomized design (CRD) with two treatments of local and import beef atnine markets as the location and taken three times in each market. The variables observed were the physical qualityof meat (pH, cooking lose of meat, water holding capacity, meat color) and chemical quality i.e. protein level, meatcontent of water and microbial profile (total of microbe, E.coli and Coliform). The results showed that pH of localbeef, cooking shrinkage, water holding capacity, meat protein were 20.37% (P <0.01), 10.11% (P> 0.05), 50.62%( P <0.01) and 9.08% (P <0.05) were lower than imported beef while the meat color and meat moisture contentwere higher by 35.14% (P <0.01) and 53% (P> 0.05), respectively. Total microbe of local beef, total E. coli of meatand total of Coliform respectively 45.16% (P <0.05), 79.59% (P <0.05) and 51% (P <0.05) markedly higher thanimported beef. It can be concluded that the means showed good quality of physical local and import beef and existedin the normal score, so they can be consumed. However, total microbe of local and import beef, especially E.coli andColiform were above standard except E.coli on import beef which was still under the standard of SNI.3932:2008.